Perbedaan Efektivitas Progressive Muscle Relaxation (PMR) dengan Slow Deep Breathing Exercise (SDBE) terhadap Tekanan Darah Penderita Hipertensi - Andry Sartika; Anwar Wardi; Yani Sofiani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aimed to determine the differences between the effectiveness of Progressive Muscle Relaxation (PMR) and Slow Deep Breathing Exercise (SDBE) on BP of hypertension patients. The research was an experiment with a randomized pretest and posttest with three group design without a control group. There was no significant difference on the effectiveness between the three groups after intervention. The optimal time of reduction in systolic BP in the PMR and SDBE groups occurred on day three. In diastolic BP, the optimal time of reduction did not occured. Conclusion, the three relaxation techniques effectively reduced blood pressure of hypertension patients.The effective time of blood pressure reduction occurred on the third day. Keywords: Hypertension, Progressive Muscle Relaxation (PMR), Slow Deep Breathing Exercise (SDBE), Blood Pressure